Modeling and numerical studies of selective laser melting: Multiphase flow, solidification and heat transfer. (November 2020) - He, Qiyang; Xia, Huanxiong; Liu, Jianhua; Ao, Xiaohui; Lin, Shengxiang
Abstract: A multiphase and multi-physics model is developed for the selective laser melting process, where fluid flow, solidification, and heat transfer are included. The discrete-element and volume-of-fluid methods are applied to generate the powder bed and capture the free surface of the melts, respectively. Physical behaviors like surface tension, Marangoni effect, vapor recoil, and radiation are considered. A strategy that the heat source is allowed adaptively following the free surface of a molten pool along with power leakage-free is developed for the moving laser. The fundamental characteristics of the molten pool and solidified tracks are found and analyzed. The remolten region between two neighboring tracks in the horizontal and vertical directions is predicted, and the effects of the scanning spacing and laser power on the width and depth of the remolten region are investigated. The results indicate that both the dimensions of the molten pool and remolten region depend on the process parameters anisotropically, varying the laser energy input could change the dynamic regime of a molten pool, and the pore defect can appear between adjacent tracks when using a large scanning spacing. Graphical abstract: Unlabelled Image Highlights: A multiphase and multi-physics mesoscale model for the selective laser melting process is developed. Fluid flow, heat transfer, melting/solidification are included, and surface tension, Marangoni effect, vapor recoil are taken into account. Objects with double tracks and double layers are simulated, and the remolten regions are predicted. Effects of scanning spacing and laser power on the remolten region and pore defect are examined.